2008
DOI: 10.1371/journal.pone.0001772
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Features of HIV-Associated Tuberculous Meningitis in Vietnamese Adults

Abstract: MethodsThe aim of this prospective, observational cohort study was to determine the clinical and microbiological features, outcome, and baseline variables predictive of death, in Vietnamese adults with HIV-associated tuberculous meningitis (TBM). 58 patients were admitted to the Hospital for Tropical Diseases in Ho Chi Minh City and underwent routine clinical and laboratory assessments. Treatment was with standard antituberculous therapy and adjunctive dexamethasone; antiretroviral therapy was not routinely av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 33 publications
4
87
0
2
Order By: Relevance
“…The mortality for HIV-infected patients with TBM is alarmingly high [5,96,97]. Most patients presenting with TBM are either not receiving antiretrovirals (ARVs) or are not being effectively treated with them.…”
Section: Immune Reconstitution With Antiretroviral Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The mortality for HIV-infected patients with TBM is alarmingly high [5,96,97]. Most patients presenting with TBM are either not receiving antiretrovirals (ARVs) or are not being effectively treated with them.…”
Section: Immune Reconstitution With Antiretroviral Therapymentioning
confidence: 99%
“…Most patients presenting with TBM are either not receiving antiretrovirals (ARVs) or are not being effectively treated with them. CD4 counts of patients with TBM are typically very low (<50) [97]. For these patients, the question of timing of ART is critical.…”
Section: Immune Reconstitution With Antiretroviral Therapymentioning
confidence: 99%
“…The primary analysis of the observational cohort study and the randomized controlled trial have been previously reported (22,23). We included all patients from these studies who had M. tuberculosis isolated from the CSF and available for analysis of drug resistance: 46/58 (79%) from the cohort study and 141/253 (56%) from the RCT.…”
Section: Resultsmentioning
confidence: 99%
“…The first study was an observational cohort study of 58 HIV-associated TBM patients admitted to the Hospital for Tropical Diseases, Ho Chi Minh City (HCMC), between November 2004 and September 2005 (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation